Strengthening Household Economic Resilience through Islamic Financial Literacy and Investment Training for PKK Women in Karangmulya Village - Siti Nursaidah; Purnama Putra; Ummi Khoiriyah; Dian Desty Wdyowati; Puput Putrianika (Santoso Academy Network, 2026)
Low financial literacy among rural women in Indonesia, especially housewives, remains a major barrier to improving family welfare. This community service program aimed to strengthen family economic capacity through financial education and Islamic investment training for PKK (Family Welfare Empowerment) members in Karangmulya Village. The main issues identified were limited knowledge of household financial management and low awareness of legal, safe, and affordable Islamic investment instruments. Conducted in February 2025, the program applied participatory training methods, including interactive lectures, focus group discussions, budgeting simulations, and hands-on Islamic investment practice using the Bibit platform. Program evaluation employed pre-test and post-test assessments, participant observation, and feedback surveys. The results showed significant improvement in participants’ financial literacy, particularly in budgeting, saving, emergency fund planning, and understanding Islamic investment concepts. Participants also gained greater confidence in managing household finances and showed increased interest in starting small-scale investments. Several participants independently formed financial learning groups after the program. These findings indicate that community-based Islamic financial education can effectively enhance financial awareness and promote more inclusive household financial behavior among rural women. Integrating Islamic financial education into regular PKK activities can support sustainable community economic empowerment.